(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Concrete is a combination of Cement, Natural sand, and Aggregates. Cement is a binding property and a mixture of several chemical compounds. Aggregates are granites which are indigenous rocks which are excessively available. Natural sand is river sand which is declining day by day and its utilization is increasing day by day. Because of this reason it is especially important to find an alternative for this problem. Dismantled RCC structure produce heavy concrete waste is a waste. This is abundantly available and usually dumped in the earth’s crust, due to which fertility of the soil decrease and land becomes useless, to avoid this kind of problems concrete waste can be reused in the concrete and can be used in construction. Concrete waste can be partially replaced as coarse aggregate in construction. Based upon the requirement we can change the % of CA replaced by RCA so that the construction becomes economical, we can also use 100% RCA as CA for concrete walls used as partisan walls as there will be no loads on the structure